The big angry roar - Lambert, Jonny (London little tiger press, 2020)
Cub is angry, so he stomps and smashes and roars! But now he just feels worse! Maybe his friends can help? The perfect story for any child experiencing feelings of anger and learning what to do with them
Educational stories
Keywords: Educational stories